ANALISIS GENDER TERHADAP KECEMASAN MATEMATIKA DAN SELF EFFICACY SISWA - Siti Imro’ah; Widodo Winarso; Edi Prio Baskoro (KALAMATIKA Jurnal Pendidikan Matematika, 2019)
Both male and female students tend to experience anxiety when learning mathematics. Mathematical anxiety can be overcome by each student depending on the student's self-efficacy. The level of mathematical anxiety and the ability of self-efficacy are assumed to have different tendencies when viewed from a gender perspective. So, this study aims to analyze mathematical anxiety and self-efficacy based on gender differences. The method used in this study is a quantitative method with comparative causal research design. The population in this study were students of Junior High School, with Cluster Sampling techniques obtained by 38 students as the research sample. The instrument used was a questionnaire. with data analysis techniques using independent sample t-test. Based on the results of the study, it has a small tendency towards mathematical anxiety between male and female students. where female students are more anxious when compared to male students. Whereas in student self-efficacy there is no difference between male and female students.